Description of Piscicapillaria bursata sp. nov. (Capillariidae) and Redescription of Parascarophis sphyrnae Campana-Rouget, 1955 (Cystidicolidae), Two Nematode Parasites of Hammerhead Sharks (Sphyrna spp.) off Australia - Moravec, František; Barton, Diane P (Acta parasitologica, 2019)
PURPOSE: Data on helminth parasites in hammerhead sharks are scarce and, therefore, new examinations of these hosts are needed to recognize the species composition of their parasites, including nematodes. METHODS: Helminthological examinations of hammerhead sharks, Sphyrna lewini (Griffith et Smith) (209 specimens) and Sphyrna mokarran (Rüppell) (57 specimens) (Sphyrnidae, Carcharhiniformes), from off the northern coast of Australia revealed one new and one insufficiently known species of intestinal nematode parasites. These were studied with the use of light and scanning electron microscopy. RESULTS: Both nematode species are described. Piscicapillaria bursata sp. nov. (Capillariidae) from S. mokarran (type host) and S. lewini differs from its congeners mainly in the spicule length (330 µm), body length of gravid females 12.80-21.26 mm and in possessing a subterminal female anus. The specimens of Parascarophis sphyrnae Campana-Rouget, 1955 (Cystidicolidae) (type species of Parascarophis Campana-Rouget, 1955) collected from S. lewini made it possible to redescribe the female and, for the first time, to describe the male; the same species was also found in S. mokarran. Amended diagnosis of Parascarophis is provided. Parascarophis is mainly characterized by the presence of lateral alae, a unique feature within the Cystidicolidae, and by the cephalic structures (presence of a cuticular hood and a pair of anterolateral plate-like structures in the mouth). CONCLUSIONS: In addition to the discovery of a new nematode species, Pi. bursata sp. nov., the finding of Pa. sphyrnae in Australian waters represents a new geographical record of this parasite outside the Atlantic Ocean. The species of Parascarophis previously described from teleosts, P. bharatii Agrawal, 1965, P. oteroi Arya, 1992 and P. mulloidi Imam, Tawfik et Abdel Hady, 1982, are designated as species inquirendae and incertae sedis. The finding of P. sphyrnae in Australian waters represents a new geographical record of this parasite outside the Atlantic Ocean. Pa. sphyrnae had not been reported previously from beyond the Atlantic Ocean.
Keywords: hlístice; Austrálie; Male; parazitární nemoci střev; Fish Diseases; Nematoda; mužské pohlaví; Australian waters; žraloci; Animals; Intestinal Diseases, Parasitic; ženské pohlaví; nematodózy; zvířata; nemoci ryb; Trichinelloidea; Habronematoidea; Nematode Infections; Sharks; Female; Sphyrnidae; Parasitic nematode; Australia